Navigating Vulnerability in the Context of Resettlement: Syrian Youth in Türkiye - Kılınçarslan, Pelin; Dalkıran, Müge; İçduygu, Ahmet (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
This article explores vulnerability in the resettlement experiences and imaginaries of Syrian refugee youth (aged 18–35) in Türkiye, a group often excluded from conventional vulnerability frameworks. Based on in-depth interviews, it conceptualizes vulnerability as multi-faceted, spanning innate, structural, and situational dimensions. Findings show how shifting migration policies, politicization, and institutional barriers compound insecurities, shaping how youth imagine and pursue resettlement in a protracted refugee context. The study contributes to debates on vulnerability, youth migration, and the evolving possibilities of resettlement, and underlines the need for international policies and agreements that adopt context-sensitive approaches addressing structural and situational factors.